The Hungarian experience in economic planning : a theoretical and empirical study - Balassa, Bela A. (New Haven : Yale University Press, 1959)
The book deals with the theoretical model of central planning based on physical allocation of resources, and examines the functioning of the performance of the Hungarian economy by means of a set of success indicators.
Includes bibliographical references and index.
gp 21/01/2019
Loans
Keywords: Economic policy; Hungary